(2,2′-Bipyridine-κ(2) N,N′)(4-hydroxy-2-oxidobenzaldehyde thiosemicarbazonato-κ(3) O (2),N (1),S)zinc(II) - Tan, Kong Wai (International Union of Crystallography, 2009)
The Zn(II) atom in the title compound, [Zn(C(8)H(7)N(3)O(2)S)(C(10)H(8)N(2))], is N,N′-chelated by the heterocycle and N,O,S-chelated by the doubly deprotonated Schiff base ligand in a distorted square-pyramidal environment. O—H⋯O and N—H⋯N hydrogen bonds link adjacent molecules into a layer structure.